(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
In this paper, we proved some existence theorems of fixed points for monotone nonspreading mappings \(T\) in a Banach space \(E\) with the partial order \(≤\). In order to finding a fixed point of such a mapping \(T\), moreover we proved the convergence theorem of Mann iterative schemes under the condition \(_n=1^∞β_n(1-β_n)=∞\), which contain \(β_n=1n+1\) as a special case.